Perceived income inequality and subjective social status in Europe - Gábor Hajdu (Global Labor Organization (GLO), 2021)
This paper analyzes how perceived income inequality is associated with subjective well-being. Using four waves of the "Social Inequality" module of the International Social Survey Programme, I show that the higher the level of perceived income inequality is, the lower the individual's perception of her social standing, even if objective income inequality and preferences for the legitimate level of income inequality are controlled for. The results are robust to the measure of perceived inequality and the choice of the outcome variable. The analysis also provides evidence that the estimated association is weaker for individuals with higher income, higher education, and countries without postcommunist history. Overall, the results suggest that not only do objective inequality and perception of fairness have consequences regarding subjective well-being but also the perceived level of income inequality itself.
Keywords: D31; D63; I31; J31; 330; inequality perception; income inequality; subjective social status; subjective well-being